2012
DOI: 10.1021/jz3015869
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-Induced Crumpling of Graphene Oxide Nanosheets in Aerosolized Droplets: Confinement Force Relationship

Abstract: A possible solution to solve the restacking issue of graphene oxide (GO) nanosheets during large-scale production is to turn the two-dimensional (2D) nanosheets into three-dimensional (3D) crumpled balls that have excellent compressive properties but still maintain high free volumes. An aerosol-based process has been proven to be a rational method for this purpose, in which, the crumpling phenomenon, however, has hitherto remained unclear. Here we present a detailed understanding of the crumpling of GO nanoshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
170
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(172 citation statements)
references
References 30 publications
2
170
0
Order By: Relevance
“…By searching the literature, we found that many other nanoparticles produced wrinkles on GO as well. 13,[30][31][32][33][34] Our own experiment also indicated that silica nanoparticles can produce very obvious wrinkling ( Figure S2A). On the other hand, if GO is dried by itself, no extensive wrinkling was observed ( Figure 2F).…”
mentioning
confidence: 70%
“…By searching the literature, we found that many other nanoparticles produced wrinkles on GO as well. 13,[30][31][32][33][34] Our own experiment also indicated that silica nanoparticles can produce very obvious wrinkling ( Figure S2A). On the other hand, if GO is dried by itself, no extensive wrinkling was observed ( Figure 2F).…”
mentioning
confidence: 70%
“…The modified Hummers method was used to make GO from graphite (Hummers, 1958;Wang et al, 2012b). First, graphite powder (45 lm; Sigma-Aldrich) was oxidized with potassium permanganate in the presence of sulfuric acid (H 2 SO 4 ) at 0°C.…”
Section: Go Synthesismentioning
confidence: 99%
“…However, the flat morphology of graphene sheets can be problematic, as the strong van der Waals attraction between layers can lead to aggregation and reduction of effective surface area (Luo et al, 2011). One possible solution is to turn the two-dimensional (2D) nanosheets into three-dimensional crumpled balls by aerosol techniques (Luo et al, 2011;Wang et al, 2012b). Crumpling the flat morphology of graphene oxide (GO) nanosheets enables the harnessing of the large specific surface area without compromising the desirable electrical properties (Stankovich et al, 2006;Ma et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The applied energy is utilized in undertaking plastic work that enhances the ability of graphene to absorb more energy [77]. Graphene has shown inclination for stable folding and bending energy at folds is compensated by intersheet adhesion (Van der Waals interactions) [78] [79]. The individual layers of graphene, under external loadings and thermal stresses, undergo out-ofplane wrapping [80] [81], rippling [82] [83], folding [84] [85], scrolling [86] [87], and crumpling [88] [89], making graphene suitable to enhance the toughness of polymers.…”
Section: Topographical Featuresmentioning
confidence: 99%